2022
DOI: 10.1093/jhered/esac035
|View full text |Cite
|
Sign up to set email alerts
|

Demographic inference provides insights into the extirpation and ecological dominance of eusocial snapping shrimps

Abstract: Although eusocial animals often achieve ecological dominance in the ecosystems where they occur, many populations are unstable, resulting in local extinction. Both patterns may be linked to the characteristic demography of eusocial species—high reproductive skew and reproductive division of labor support stable effective population sizes that make eusocial groups more competitive in some species, but also lower effective population sizes that increase susceptibility to population collapse in others. Here, we e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…In humans, benevolent social activities, such as modern health care, are thought to have led to the accumulation of deleterious mutations within populations [4,5]. Moreover, the capacity for co-operative brood care in insect societies to maintain and/or buffer against extreme changes in effective population size is thought to be a key determinant of population stability [68]. Therefore, the extent to which genetic variation is affected by social behaviour has implications for the health of populations and their capacity to rapidly adapt to environmental perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, benevolent social activities, such as modern health care, are thought to have led to the accumulation of deleterious mutations within populations [4,5]. Moreover, the capacity for co-operative brood care in insect societies to maintain and/or buffer against extreme changes in effective population size is thought to be a key determinant of population stability [68]. Therefore, the extent to which genetic variation is affected by social behaviour has implications for the health of populations and their capacity to rapidly adapt to environmental perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Population genetic theory predicts that genetic diversity will increase with Ne and mutation rate ( Charlesworth, 2009 ). Previous empirical work linking behavioral and life-history traits, such as reproductive strategy, fecundity, and body size with genetic diversity has suggested that these associations are ultimately mediated by changes in Ne ( Bharti et al, 2023 ; Chak et al, 2022 ; Romiguier et al, 2014 ; Settepani et al, 2017 ). However, our results cannot be explained by demography because populations were maintained at similar population sizes with no differences in fecundity ( Schrader, 2017 ) and no possibility of overlapping generations and/or changes in mating structure.…”
Section: Discussionmentioning
confidence: 99%